READY-MADE GARMENT SECTOR AND INTERNATIONAL TRADE DEVELOPMENT: EVIDENCE FROM BANGLADESH - Mohammad Nazim Uddin; Mustafa Manir Chowdhury; Mohammad Jonead Kabir; Habib Ullah (Universitas Trisakti, 2014)
The Ready-made garment sector has occupied an important place in international trade of Bangladesh. The main purpose of the study is to examine the contribution of RMG sector for the development of international trade in Bangladesh. The study has used primary and secondary data. In order to collect primary data, two sets of questionnaires are developed, which are prepared in the light of the objectives of the study. The study has also used secondary data only relevant to the export value of RMG sector, total export value of the country, total import value of RMG sector, import value of the country, balance of trade, and balance of payment etc. for measuring the international trade development in Bangladesh during the period of 2003- 2013. The main reason to consider the certain period is the availability of data. This study revealed that the RMG sector has made substantial contribution for the development of International trade in Bangladesh. The result of the study also indicates that the RMG sector in the country has brought the largest part of export earnings that minimize the trade deficit. But there are some realistic problems in the RMG sector that hinder the development of international trade. The study seems to carry an enormous academic value since a few studies have been undertaken in this area. It may be helpful to the RMG entrepreneurs, BGMEA, Export promotion bureau (EPB), Academic researchers and national policy makers who have been making endeavor to the development of RMG sector as well as development of international trade as a whole.Key words: RMG sector, Export value, Balance of trade, foreign reserve and International trade development